PENETAPAN BATAS DARAT INDONESIA – MALAYSIA DAN IMPLIKASINYA TERHADAP KETAHANAN WILAYAH ( Studi Pada Peran Direktorat Topografi TNI AD Dalam Penetapan Batas Darat Indonesia - Malaysia Di Kecamatan Sei Menggaris Kabupaten Nunukan Provinsi Kalimantan Utara ) - Susilo, Hendri; Ritohardoyo, Su; Zubaidi, Ahmad (Magister Ilmu Administrasi Negara Universitas Mulawarman, 2018)
This study discussed the determination of Indonesia-Malaysia land border and its implications for regional resilience (A Study of Roles of the Directorate of Topography of the Indonesian Army in the Determination of Indonesia-Malaysia Land Border in Sei Menggaris Nunukan North Kalimantan). This research applied the qualitative research method. Data collection methods were observations, in-depth interviews, documents and literatures review, and online data tracking. The findings indicated that roles of the Directorate of Topography of the Indonesian Army in the determination of Indonesia-Malaysia land border included border demarcation and Investigation, Refixation, and Maintenance (IRM) of Indonesia-Malaysia border. The determination of Indonesia-Malaysia land border strengthened the regional resilience of Sei Menggaris Nunukan North Kalimantan. Kata Kunci : Land Border, Roles, Regional Resilience